EXAMİNİNG THE ENTREPRENEURSHİP LEVELS OF STUDENTS WHO PLAY/DO NOT PLAY SPORTS - Münire Burcu PORDOĞAN; Sevim GÜLLÜ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The purpose of this research is to examine the entrepreneurship levels of university students who play/do not play sports. The research was conducted in the survey model. Scales including questions about participant demographics and entrepreneurship levels were applied to the students. The Entrepreneurship Scale was acquired from Özman (2013). Percentage, frequency, and crosstab methods were used to determine the distribution of participant demographics. To test whether the subdimensions of the scale exhibit normal distribution, The Kolmogorov-Smirnov test was performed and it was found that the entrepreneurship scale exhibited normal distribution. (p<0.05). Accordingly, the independent t-test and the one-way variance (ANOVA) test were applied for two-variable data at the significance level of α = 0.05 and multi-variable data respectively. Post-hoc tests were utilized to find the difference between the groups. The study group of the search was composed of fourth-year female and male students who were attending the School of Business Administration and the fourth-year female and male students who were attending at the Department of Sports Administration and Coaching Education at İstanbul University. The total number of the participants was 107. According to the results obtained from the findings, 52.3% of the participants reported that they do not play sports while 17% reported that they do plays ports. The entrepreneurship levels of the participants did not differ significantly based on whether they play/do not play sports. As a result, no variables within the scope of the research affected the entrepreneurship levels of the participants.